2008
DOI: 10.1016/j.mri.2008.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Bias of cartilage T2 values related to method of calculation

Abstract: Purpose-To determine how different methods for calculating T 2 affect the resulting T 2 values of patellar cartilage.Materials and Methods-T 2 -weighted images of patellar cartilage for 10 subjects were acquired using 2 MRI scanners. T 2 values of patellar cartilage were calculated using linear, weighted and nonlinear fitting algorithms for a mono-exponential decay equation. T 2 values were also calculated for the superficial, middle and deep zones of the cartilage Results-All three methods of calculation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 41 publications
0
35
0
Order By: Relevance
“…Therefore, the sensitivity of T2 mapping to detect pathology in cartilage tissue may be improved by using an adequate fitting method [25]. Koff et al [26] found that linear, weighted and non-linear fitting algorithms resulted in significantly different T2 values (p < 0.0001). The non-linear calculation demonstrated the lowest T2 values, the linear calculation resulted intermediate T2 values and the weighted calculation resulted in the highest T2 values [26].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the sensitivity of T2 mapping to detect pathology in cartilage tissue may be improved by using an adequate fitting method [25]. Koff et al [26] found that linear, weighted and non-linear fitting algorithms resulted in significantly different T2 values (p < 0.0001). The non-linear calculation demonstrated the lowest T2 values, the linear calculation resulted intermediate T2 values and the weighted calculation resulted in the highest T2 values [26].…”
Section: Discussionmentioning
confidence: 99%
“…1). Then, m(0) and σ(0) at the zero echo time are estimated by the mono-exponential model [8,9] (red curves in Fig. 1).…”
Section: Multi-echo Based Noise Removing Methodsmentioning
confidence: 99%
“…The global mean and the standard deviation at the zero echo time, m(0) and σ(0), are estimated using the method proposed by Koff et al [8].…”
Section: Multi-echo Based Noise Removing Methodsmentioning
confidence: 99%
“…To solve the equation for T2 and S 0 , different fitting methods such as linear least squares, weighted linear least squares, or nonlinear least squares algorithms were used in the past [10,20]. The chosen fitting method has a considerable impact on the resulting T2 values, thus making the comparison of T2 values of different studies using different fitting methods difficult.…”
Section: T2 Relaxation Time Measurementsmentioning
confidence: 99%
“…Various possibilities for the number and values of the echo times (TE) were reported. To give an example, the Osteoarthritis Initiative (OAI), which had 4,796 study participants, used a multislice multiecho (MSME) spin echo sequence with seven echoes (TE = 10,20,30,40,50,60, and 70 ms), repetition time (TR) of 2,700 ms, and total acquisition time of 10.6 min [9].Compared to single-echo spin echo and single-slice multiecho spin echo sequences, the application of a MSME spin echo sequence considerably reduces the acquisition time. This is important for the feasibility of quantitative T2 relaxation time measurements in clinical practice.…”
mentioning
confidence: 99%